Relations between the Dark Tetrad traits and subjective indicators of career success - Ilić, Dunja; Dinić, Bojana M. (Psihološka istraživanja, 2023)
This research aimed to examine the relations between Dark Tetrad traits (Machiavellianism, narcissism, psychopathy, and sadism) and subjective indicators of career success (job and career satisfaction), considering their multidimensionality. The sample consisted of 227 employees (27% male) on which followed instruments were applied: Serbian adaptations of the Job Satisfaction Survey, the Career Satisfaction Scale, the Mach-IV, the Narcissistic Admiration and Rivalry Questionnaire, the Levenson Self-Report Psychopathy Scale, and the Short Scale of Sadistic Impulses. A hierarchical regression analysis was applied, with demographic characteristics (gender, level of education, work tenure) in the first block of predictors, to control their effects, and Dark Tetrad traits in the second block, while criteria were various aspects of the job and career satisfaction. The results showed that Machiavellianism was the dominant negative predictor of subjective indicators of career success, especially the nature of work and communication within the organization, while secondary psychopathy showed a significant negative effect on satisfaction with communication. Narcissistic admiration was related to dissatisfaction with working conditions and relationships with coworkers. Primary psychopathy, narcissistic rivalry, and sadism did not show a significant contribution to subjective career success, although they showed negative correlations with satisfaction with coworkers.
Keywords: Dark Tetrad; Dark Triad; job satisfaction; career satisfaction; career success; employees